Fractionation and Homogenization of Recuperated Pulp Fibers from Brazilian Paper and Pulp Industry - Pieter Samyn (Environmental Sciences Proceedings, 2021)
With a projected growth of the Brazilian pulp and paper industry of about 20% over the period 2020–2025, the innovations in waste management and utilization of side-products originating from the pulp and paper industry may mostly contribute to sustainable development of forest-based products, e.g., by implementing the recuperation and innovative processing of side-stream products at a local level. In this study, we analyze the feasibility for the reuse of recovered cellulosic fibers collected from pulp and paper mill sludge by considering some practical issues and evaluation of the quality for different side-stream fractions originating from rejects, deinking sludge, primary sludge, and secondary sludge. The situation for the Brazilian pulp and paper industry will be used as a model, for which the potential for recovery of fibers from wastewaters will be evaluated from the analysis of available data. First, the water consumption and effluents from paper mills are reviewed together with an estimation of the fiber recovery potential from primary sludge and fine fiber rejects. Second, the specific characteristics and appearance of certain fiber fractions might imply constraints on their further processing properties. Therefore, we describe some insights into the fiber fractions that could provide the highest potential for future valorization. Based on the degree of compositional homogeneity and concentration of cellulose fibers in several waste fractions, the processing of fibers from primary sludge and/or fine fiber rejects is estimated as the most economically feasible. The homogenization of the fiber fractions yields fibrillated cellulose materials with various morphologies depending on the selection of recuperated fractions. Through thorough characterization of the resulting fiber fraction, new application markets can be selected.